Echocardiographic features of bioprosthetic valve endocarditis. Issue 3 (March 1984) - Nagata, S; Park, Y D; Nagae, K; Beppu, S; Kawazoe, K; Fujita, T; Sakakibara, H; Nimura, Y
Abstract : Abnormal echocardiographic findings in seven cases of bioprosthetic valve endocarditis were confirmed in six at operation. The echocardiograms showed three cases with thickening and increased echo intensity (group 1) and four (group 2) in which vegetations were seen initially without either of the two features in group 1. Two patients in group 1 had vegetations, the causative organism being a streptococcus. Staphylococcus epidermidis was the causative organism in three of the four cases in group 2; in two of these rapidly growing vegetations were detected. The large vegetations obstructed the ostium of the bioprosthetic valve. Thus if vegetations are detected in cases in which staphylococci are the causative bacteria surgery should be performed as soon as possible. In patients who develop a fever after bioprosthetic valve replacement and especially in those with evident bacteraemia echocardiography should be repeated frequently so that lesions may be detected early.